HIV-1 tropism in low-level viral load HIV-1 infections during HAART in Guangdong, China - Zhang, Chuyu; Lan, Yun; Li, Linghua; He, Ruiying; Meng, Yu; Li, Jian; Chen, Weilie (Frontiers in Microbiology, 2023)
Background: Since only a few studies have been conducted on the factors associated with different HIV-1 tropisms in low-level viral load HIV-1 infections in China, we investigated HIV-1 V3 loop in prevalent HIV-1 subtypes and factors related to HIV-1 tropism and immune recovery in HIV-1 infections after 6 months of highly active antiretroviral therapy (HAART) in Guangdong, China. Methods: Plasma samples with HIV-1 RNA of 400–999 copies/mL were collected. We analyzed the sequence of the V3 loop by in silico prediction algorithms. Mann-Whitney and Chi-square tests were used for statistical comparison. Furthermore, logistic regression and multiple linear regression were used respectively for factors associated with 351 HIV-1 tropism and immune recovery of 67 cases with continued CD4+ T cell count during HAART. Results: There was a lower percentage of HIV-1 R5-tropic virus in CRF01_AE (66.3%) (P < 0.0001) and CRF55_01B (52.6%) (P < 0.0001) compared with both CRF07_BC (96.1%) and CRF08_BC (97.4%), respectively. Compared with the R5-tropic virus, higher proportions of IIe8/Val8, Arg11/Lys11, and Arg18/His18/Lys18 were observed in the X4-tropic virus of CRF01_AE and CRF07_BC (P < 0.0001). The baseline CD4+ T cell count (P < 0.0001) and baseline CD4+ T/CD8+ T ratio (P = 0.0006) of all R5-tropic infections were higher than those in the X4-tropic infection. The baseline CD4+ T cell count (OR 0.9963, P = 0.0097), CRF07_BC (OR 0.1283, P = 0.0002), and CRF08_BC (OR 0.1124, P = 0.0381) were associated with less HIV-1 X4-tropism. The baseline CD4+ T cell count was a positive factor (P < 0.0001) in the recovery of CD4+ T cell count during HAART. Conclusion: R5-tropism represented the majority in low-level viral load HIV-1 infections receiving HAART for more than 6 months in Guangdong, China. The baseline immune level in the HIV-1 R5-tropic infections was higher than that in the X4-tropic infections. The amino acids of the 8th, 11th, and 18th of the HIV-1 V3 loop were more variable in the X4-tropic HIV-1. CRF01_AE, CRF55_01B, and lower baseline CD4+ T cell count were associated with more HIV-1 X4-tropism. The immune recovery during HAART was positively related to baseline CD4+ T cell count.